Determinants and effects of non-farm enterprise diversification on household economic wellbeing in rural Nigeria - Abdul Aziz, Sheehu; Ahmad Sidique, Shaufique Fahmi; Said, Rusmawati (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
This paper examines the determinants of non-farm enterprise (NFE) diversification decision among farm households in rural Nigeria and its effects on their economic wellbeing. By employing probit model, we find that NFE diversification decision significantly depends on household head’s education, household size, and community level infrastructures. The model also indicates that households residing closer to markets are more likely to diversify into NFE activities than those in remote areas. Unique to this study, we find that households having access to social and financial capital can overcome the entry barriers associated with NFE diversification. Propensity score matching technique was used to assess the impact of NFE diversification on household economic wellbeing, using annual total consumption expenditure and food shortage status of the household as indicators of economic wellbeing. The result reveals that NFE diversification has a significant positive impact on consumption expenditure and food availability. This suggests that NFE diversification could be a pathway for improving the economic wellbeing of farm households in rural areas of developing countries.